2012
DOI: 10.1017/s0025315412000537
|View full text |Cite
|
Sign up to set email alerts
|

A review of the infectious agents, parasites, pathogens and commensals of European cockles (Cerastoderma eduleandC. glaucum)

Abstract: A systematic review of the parasites, pathogens and commensals of the edible cockle (Cerastoderma edule) and of the lagoon cockle (Cerastoderma glaucum) has been completed. A total of 59 different conditions have been reported throughout the range of both of these hosts; of these 50 have been reported in edible cockles, and 28 in lagoon cockles. Cockles are hosts to viruses, bacteria, fungi (including Microsporidia), Apicomplexa, Amoeba, Ciliophora, Perkinsozoa, Haplosporidia, Cercozoa, Turbellaria, Digenea, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 157 publications
(255 reference statements)
0
36
0
Order By: Relevance
“…Previous records of Minchinia spp. in the UK are from a histopathology survey of cockles (Longshaw and Malham, 2012), which suggested that Minchinia mercenariae and M. tapetis may be implicated in host population crashes. Our results provide the first molecular records of Minchinia in the UK.…”
Section: Phylogenetic Patternsmentioning
confidence: 99%
“…Previous records of Minchinia spp. in the UK are from a histopathology survey of cockles (Longshaw and Malham, 2012), which suggested that Minchinia mercenariae and M. tapetis may be implicated in host population crashes. Our results provide the first molecular records of Minchinia in the UK.…”
Section: Phylogenetic Patternsmentioning
confidence: 99%
“…Histological analysis does not allow species identification. Two species of this genus, N. portunidarum and N. incognito, have been described from C. glaucum (Longshaw & Malham 2013). Nematopsis sp.…”
Section: Discussionmentioning
confidence: 99%
“…Another unidentified coccidian-like organism that caused no serious histological damage was observed in the gills of lagoon cockles; this organism was found in more sampled beds than were the organisms infecting the kidney. No reports of coccidians infecting gills of cockles were included in the review by Longshaw & Malham (2013); a coccidian-like protist was seen in the gills of razor clams Ensis siliqua (Ruiz et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations